ИССЛЕДОВАНИЕ ДЕГРАДАЦИИ СОЛНЕЧНЫХ ЭЛЕМЕНТОВ НА ОСНОВЕ ПОЛИКРИСТАЛЛИЧЕСКОГО КРЕМНИЯ - Исмайлов, К.А.; Косбергенов, Е.Ж. (SCIENCE and SOCIETY, 2020)
The article presents experimental studies and calculations of the degradation of solar cells based on polycrystalline silicon under the influence of light and temperature. The results of the effect of additional doping with nickel atoms on the degradation of solar cells are presented.
Keywords: silicon solar cell; degradation; voltage temperature coefficient; polycrystalline silicon